(untitled) - Avroy A Fanaroff (Philadelphia, 1993)
In this edition some sections have been eliminated, others added, and new authors brought into the fold. It has been strengthened by the addition of a section dealing with some of the ethical problems that confront the perinatal team as well as of a chapter that addresses the complex issues unique to neonatal nursing.
Keywords: infant care,infants ( newborn ) - diseases,neonatal intensive care